Eurogin Roadmap 2015: How has HPV knowledge changed our practice: Vaccines. Issue 3 (22nd March 2016) - Brotherton, Julia M.L.; Jit, Mark; Gravitt, Patti E.; Brisson, Marc; Kreimer, Aimée R.; Pai, Sara I.; Fakhry, Carole; Monsonego, Joseph; Franceschi, Silvia
Abstract : This review is one of two complementary reviews that have been prepared in the framework of the Eurogin Roadmap 2015 to evaluate how knowledge about HPV is changing practices in HPV infection and disease control through vaccination and screening. In this review of HPV vaccine knowledge, we present the most significant findings of the past year which have contributed to our knowledge of the two HPV prophylactic vaccines currently in widespread use and about the recently licensed nonavalent HPV vaccine. Whereas anal cancer is dealt with in the companion mini‐review on screening, we also review here the rapidly evolving evidence regarding HPV‐associated head and neck cancer and priority research areas. Abstract : What's new? Ten years since the licensing of HPV vaccines, evidence of their efficacy, safety, and potential cost‐effectiveness has continued to grow; we have also seen the fruit of efforts to develop vaccines that target a broader number of HPV types. Despite efforts to decrease vaccine price, the implementation of HPV vaccination worldwide remains a considerable challenge on account of insufficient political commitment, competing priorities in poor countries, and remaining problems with vaccine hesitancy.